Multinational production and intra-firm trade - Vanessa Alviarez; Ayhab Saad (Inter-American Development Bank (IDB), 2022)
Intra-firm trade, from parents to affiliates, has been combined with standard models of multinational production (MP) to deliver gravity-style predictions for foreign affiliates' sales. Nonetheless, the evidence shows that intra-firm trade is concentrated among a small set of large multinational firms. Using firm-level data from 35 countries, we document that only firms belonging to multinational corporations (MNCs) in the upper tail of the firm's size distribution are significantly affected by the distance to their parents. We present a simple framework featuring MNCs' selection into intra-firm trade and derive the analytical gravity equations that are consistent with the empirical findings.
Keywords: F12; F23; 330; Intra-firm trade; Multinational production